Kinetic study of Aquilaria Malaccensis leaves by using vacuum Far infrared dryer / Muhammad Naqib Azizan - Azizan, Muhammad Naqib (2018)
In this study, Far infrared drying behavior of Aquilaria Malaccensis leaves was investigated in advanced of vacuum pressure. The study was aimed to study the effect of VFIR drying in terms of changes of color, moisture content, drying curve and mathematical model. in addition, this would results in less energy conserved, less damaging drying process and contribute the originality of the product. The parameter of this experiment is set to be temperature of 40°C, 50°C and 60°C under vacuum pressure of 5 bar with drying time of 120 minutes long. the drying data were fitted to 3 thin layer drying models. The performance of these models were compared using the determination of coefficient, R², reduced chi square, X²and root mean square error, RMSE between the experimental and predicted of moisture content. The mathematical model give a results of Page that the most suitable in analyzing drying curve of Aquilaria Malaccensis.